To Correlate the Serum Levels of Adiponectin with Systolic and Diastolic Blood Pressure in Hypertensive’s and Healthy Individuals (Medical Forum Monthly, 2024)
Background: To correlate the serum levels of adiponectin with systolic and diastolic blood pressure in hypertensive’s and healthy individuals.Study Design: Cross-sectional, case control study.Place and Duration of study: This study was conducted at the Department of Physiology BMSI JPMC in colaboration with Abassi Shaheed hospital karachi from Dec 2008 to June 2009.Materials and Methods: This study included total 100 subjects, 50 subjects with known case of hypertension and 50 normal healthy age and gender matched controlsResults: Adiponectin serum concentration was found lower in coronary artery disease patients when compared with control subjects. (7.10 ) verses (11.98).Conclusion: This suggests that higher levels of serum adiponectin is protective against the development of hypertension.